Freezing Treatments for Ectomyelois ceratoniae Mortality and Maintenance of Deglet Noor Palm Date Quality - Rihab Ben-Amor; María Dolores de Miguel-Gómez; Dhouibi Mohamed Habib; Hermi Nouha; Encarna Aguayo (Journal of Food Quality)
Background. Insect infestation caused by Ectomyelois ceratoniae or carob moth is one of the main postharvest problems that can lead to a decrease of the marketable quality of dates. The control of carob moth is a mandatory process for exported fruits, and the main chemical method used to prevent pest diseases of palm date is treatment with methyl bromide. However, its use is being restricted due to direct harmful effects on the environment and indirect effects on humans. Freezing treatments could be physical alternatives to methyl bromide and other chemicals. Three freezing treatments at −18°C (50 h, 77 h, and 125 h) were studied for E. ceratoniae mortality in Deglet Noor date fruits. Results. The results showed that freezing at −18°C led to 100% mortality of all the stages of E. ceratoniae found in naturally infested dates. Fruit quality was examined under a selected sanitizing freezing treatment (50 hours at −18°C). This freezing treatment induced an increase of monosaccharides and a reduction in antioxidant activity (40 to 45%, measured with FRAP and DPPH assays). However, other parameters such as color, amino acids, total phenolic content, and microbial and sensorial quality were not affected by that treatment. All samples remained above the limit of marketability as there was no chilling injury. Conclusion. This treatment can be recommended as a green alternative to chemical treatments to control carob moth while yielding optimum-quality Deglet Noor date fruits that could be exported to developed countries.